THE LEVEL OF KNOWLEDGE REGARDING PAP-SMEAR EXAMINATION AMONG THE CHILDBEARING AGE WOMEN'S IN RW 04 RT 05, RANGKAPAN JAYA BARU, PANCORAN MAS DEPOK: DOI: https://doi.org/10.35654/ijnhs.v2i2.104 - Hendrawati Hendrawati (Alta Dharma Publisher, 2019)
Level of knowledge of women in childbearing age regarding papsmear consider low. An analytic descriptive study design was used to describe the level of knowledge regarding pap smear examination amonng the childbearing age women. Data collection tools was questionnaire in form of check list. The result confirmed that 39 from 75 participant have an excellent level of knowledge,